The Increasing Mediterranean Diet Adaptation in adults decreases energy intake: Increasing Mediterranean Diet Adaptation in adults decreases energy intake - Uçar, Zeliha; Akman , Mehmet (Progress in Nutrition, 2021)
Objective: One of the sustainable diets, the Mediterranean diet (MD) is one of the healthy diets in the world. The aim of this study is to determine the relationship between MD, one of the healthy eating models, and nutritional status in adult individuals.Methods: The study was conducted with a total of 307 individuals between the ages of 18-64 who applied to the Sakarya University Healthy Nutrition / Obesity Counseling Unit, between September 2019 and February 2020. The data were collected by face-to-face interview technique. Collected data; demographic information, 24-hour retrospective food consumption record, food consumption frequency, anthropometric measurements and Mediterranean diet compliance scale questionnaire. The average age of the individuals participating in the study is 24.7± 8.3 years for men and 24±7.1 years for women (p> 0.05).Results: According to the results obtained, individuals daily: energy (kcal), energy (kcal / kg), carbohydrate (g), carbohydrate (%), protein (%), polyunsaturated fatty acids (g), mono-saturated fatty acids (%) , saturated fatty acids (g), carotene (mg), vitamin E (mg), vitamin C (mg), vitamin K (µg) and sodium (mg) intakes were found to be statistically significant with MD (p